(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
This article analyzes the social and political processes that took place in Uzbekistan in the years after the Second World War, the measures implemented by the center on the basis of administrative command and its impact on the life of the local population. Also, in the years after the war, the changes and problems that occurred in the social support and household life of the population were analyzed on the basis of primary sources.